Comparison of dexmedetomidine and midazolam infusion for sedation in patients admitted in intensive care unit - Rajbanshi, Lalit Kumar; Arjyal, Batsalya; Bajracharya, Akriti; Khanal, Kanak; Sharma, Apurb (Journal of Chitwan Medical College, 2018)
Introduction: Dexmedetomidine and midazolam are frequently used to maintain sedation in mechanically ventilated patient in intensive care unit. The study compared dexmedetomidine and midazolam infusion in mechanically ventilated patient in terms providing effective sedation. Methods: This was one year prospective comparative study conducted in 130 mechanically ventilated patients who were randomly divided in two groups receiving either dexmedetomidine or midazolam infusion for sedation. Sedation level was assessed by Riker Sedation-Agitation Scale with the aim of maintaining target sedation score of 3 to 4. The two drugs were compared in terms of sedation level in first 24 hours, time required to achieve target sedation level, hemodynamic changes and adverse effects including ICU delirium. The outcome was measured in terms of duration of mechanical ventilation, length of ICU stays and ICU mortality. Results: Both dexmedetomidine and midazolam achieved target sedation level in a comparable time duration. The median sedation level for both the drugs was 4 and 3 in initial 4 and 24 hours respectively. Dexmedetomidne produced significant decrease in blood pressure and heart rate (P=0.044 and P=0.007 respectively). Patients treated with dexmedetomidine had less incidence of ICU delirium (odds ratio=2.669, P=0.029).Dexmedetomidine infusion had significantly shorter duration mechanical ventilation (4.10 ± 2.05 vs. 5.15 ± 2.44, P=0.011), early discharge from ICU (6.05 ± 2.02 vs. 7.48 ± 2.42, p=0.001). ICU mortality was comparable between the groups. Conclusion: Dexmedetomidine and midazolam both were equally effective in maintaining sedation in Critically ill patient. Compared to midazolam, dexmedetomidine could be a preferred sedative in ICU in terms of early removal from mechanical ventilation, early discharge from ICU and less incidence of delirium.